A new method for the electrostatic manipulation of droplet movement by triboelectric nanogenerator. (August 2021) - Sun, Xiao; Feng, Yange; Wang, Bingqiao; Liu, Ying; Wu, Zishuai; Yang, Di; Zheng, Youbin; Peng, Jialiang; Feng, Min; Wang, Daoai
Abstract: In view of the limitations of the current water droplet manipulation technology in liquid environment, a new polyaniline and polyvinylidene fluoride nanowire-based triboelectric nanogenerator (NW-TENG) is assembled to form two self-powered electrostatic manipulation systems (EMSs). Changes in the output signal of the TENG affect the strength, form, frequency, and other parameters of the electric field and result in different droplet motion behaviors because of the change in force. The unique polarization deformation mechanism of droplets in the double-electrode EMS is studied. In addition, the alternating electric field of TENG is applied to realize the reciprocating movement of the macro-charged droplets. The result shows that droplets have a shorter movement period than ordinary DC-regulated electric field (from 7.30 s to 3.67 s), and no electrical breakdown occurs. Thus, the EMS is practical and safe. The versatility of the EMS is proved by the controllable reciprocating motion of microscopic droplets (6.37 µm). Finally, a single-electrode EMS is applied to switch the adsorption and ejection of the droplets on the electrode, and an interesting step-by-step chemical reaction is realized. This work proposes a new method for manipulating the motion behavior of micro-droplets in liquid environment, which has promising potential applicability in microfluidic systems, biochemical reactions, targeted transportation and other applications. Graphical Abstract: ga1 Highlights: The motion behaviors of water droplets can be manipulated by adjusting the output signals of NW-TENG. Using this NW-TENG to manipulate the water droplets requires a lower voltage value than ordinary DC power supplies. The control of the microscopic droplet motion behavior can also be achieved.